A Tumor Microenvironments‐Adapted Polypeptide Hydrogel/Nanogel Composite Boosts Antitumor Molecularly Targeted Inhibition and Immunoactivation (Adv. Mater. 21/2022). Issue 21 (26th May 2022) - Li, Zhongmin; Xu, Weiguo; Yang, Jiazhen; Wang, Juan; Wang, Jialiang; Zhu, Ge; Li, Di; Ding, Jianxun; Sun, Tianmeng
Abstract : Sequential Drug Delivery In article number 2200449, Di Li, Jianxun Ding, Tianmeng Sun, and co‐workers develop a tumormicroenvironments‐adapted gel composite for sequential drug release to reverse the epithelial–mesenchymal transition of tumor cells and regulate the tumor immune microenvironments, thereby inhibiting tumor growth and metastases. This process is like a painter using a paintbrush to turn a depressed and cold winter into a colorful and vibrant spring.